Gasless Single Port Surgery for Renal Cell Carcinoma: Minimum Incision Endoscopic Surgery - Kihara, Kazunori; Fujii, Yasuhisa; Kawakami, Satoru; Masuda, Hitoshi; Koga, Fumitaka; Saito, Kazutaka; Numao, Noboru; Matsuoka, Yoh; Sakai, Yasuyuki (IntechOpen, 2012)
None